La psicología aplicada en la diplomacia - Galindo, Edgar (2017)
This books wants to explain the contribution of Psychology to help diplomats and other actors of international relations (international volunteers, expatriates, migrants and refugees) to accomplish their duties and/or solve their problems, exploring systematically the different ways in which psychological knowledge can be applied to analyze concrete subjects of diplomacy and policy, like decision making, perception of the others, uses of language, building of prejudices, racism, political extremism, group conflicts, negotiation, mediation, cooperation, intercultural differences, effects of war and disasters, work conditions and mental health in international & multicultural environments. It tries to build a bridge between diplomats and psychologist providing a chapter on Psychology for diplomats and one on Diplomacy for psychologists. At the same time, it has a practical goal, because the procedures and methods created by Psychology to ameliorate perceptions, cognitions and behaviors found in diplomatic work are revised